PERTANGGUNGJAWABAN NOTARIS PENGGANTI TERHADAP AKTA-AKTA DIBUATNYA YANG MERUGIKAN PIHAK KETIGA - Cahyo Adhi Nugroho (JURNAL ILMIAH HUKUM DAN DINAMIKA MASYARAKAT, 2022)
The existence of a Notary with a Substitute Notary makes a Substitute Notary also requires the same legal protection as a Notary, but in Article 66 paragraph (1) of the Law there is no mention of a Substitute Notary, so a law arises. The issues discussed are about 1) how the Substitute Notary's accountability for the deeds he makes is detrimental to third parties; 2) How is the legal protection of the Substitute Notary for the deeds he made which harms third parties; 3) and what is the position of Article 66 of Law no. 2 of 2014 for Substitute Notaries. This research is a normative juridical research using secondary data which is supported by primary data in the field. The results of the analysis are presented descriptively. The data in the field were taken through interviews with the Secretary of the Regional Supervisory Council of Semarang City and one of the Senior Notaries in the City of Semarang. The purpose of this study was to determine the legal responsibility and protection of a Substitute Notary and the position of Article 66 of the UUJN for a Substitute Notary. The results of this study 1) Substitute Notary for the deed he made that harm third parties, 2) Substitute Notary legal protection, and 3) the position of Article 66 UUJN for Substitute Notaries. The Substitute Notary has the same Article as the Notary in making the deed, namely civil and criminal obligations, the legal protection possessed by the Substitute Notary is the Obligation to Deny (verschonongsplitch) and the Right to Deny (verschoningrecht), and Provision 66 paragraph (1) UUJN does not mention that the summons of a Notary The replacement also requires prior approval from the Notary Supervisory Council (MPN). In this regard, this rule does not apply to Substitute Notaries. The suggestion from the author is that it needs to be formulated and regulated explicitly in the UUJN regarding legal protection for Substitute Notaries, and it is hoped that in the future the Right to Deny Notaries including Substitute Notaries is regulated in UUJN so that the law becomes more clearly visible.